Pengaruh Lama Perendaman Kolkisin terhadap Pertumbuhan Planlet (Chrysanthemum morifolim R) Krisan Varietas Pasopati Cara In Vitro - Arip Nursalmin; Ai Komariah; Odang Hidayat (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2018)
Laboratory-time studies to determine the duration of immersion of colchicine against growth of planlet (Krrysanthemum morifolim R) chrysanthemum varieties of in vitro way inpatients. The experiment was carried out at the Plant Biotechnology Laboratory of the Faculty of Agriculture of the University of Winaya Mukti from July to September 2017. The environmental design using Randomized Completely Random Design (RAL) consists of six treatments with 4 replications including: A (without colchicine immersion), B (immersion colcisin 1 hour, C (2-hour colchicine immersion), D (3-hour colchicine immersion), E (4-hour colchicine immersion) and F (5-hour colchicine immersion). The results showed that the duration of immersion of kolkisin on chrysanthemum varieties of pasopati in vitro gave a significant effect on the observation of the number of leaves aged 2 MST, 4 MST, 6 MST and 8 MST, the number of books aged 4 MST, 6 MST and 8 MST, root length , the number of roots as well as the height of the planlet. Immersion of 1 hour colchicine had a better effect on the observation of leaf count of age 2 MST, 4 MST, 6 MST and 8 MST, number of books aged 4 MST, 6 MST and 8 MST, root length, root number and plantlet height.